The Discrimination of Main Characters in Twain’s The Prince and The Pauper - Sahraeny, Sitti; Darmayanty,; Pammu, Abidin (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The Prince and The Pauper is one of great novels written by a famous American author, Mark Twain. The novel tells about some discrimination experienced by two main characters who were born at the same time and with similar appearance. The objectives of the writing is to investigate the kinds of the discrimination reflected by the two major characters and to elaborate the way the characters resolve the problem of discrimination. In performing the analysis, the writer utilized structural approach focusing on the intrinsic elements of literary works which are inherent in the novel. The primary data concerned text analysis that accounted primarily for literary text of the novel. This was then analyzed by means of qualitative social constructivism interpretative paradigm. Results of analysis demonstrated that social class influences the discrimination, the second was that appearance influences the discrimination, and the third was that the education also influences the existence of discrimination. Tom Canty who was born within poor family got used to deal with the discrimination. It is because he has experienced the discrimination since he was born to the world. While Edward Tudor even though he finds it difficult at the beginning to deal with discrimination finally he could afford to adjust himself with the condition. The latter had much lesson to learn from the hardship.